Fruit Tree Based Agroforestry Restoring Landscapes, Livelihoods and Lives - Balbona, Harlyn; Manipol, Mitchelle Joy; Quiñones, Alyanna Joy; Locaba, Rico; Urdelas, Farah; Anunciado, Shiela; Hellin, Jon; Rayos, Loeul; Gonsalves, Julian (International Institute of Rural Reconstruction, 2024)
Smallholder farmers are highly vulnerable to the impacts of climate change, particularly due to their reliance on agriculture, which is sensitive to climatic variations. In developing countries like the Philippines, these farmers face compounded challenges from extreme weather events, resource degradation, and socio-economic limitations such as poverty and inadequate access to social services. Climate extremes, including prolonged dry and wet seasons, threaten their crops, livelihoods, and food security, leading to significant income losses. Despite these challenges, few farmers have adjusted their farming practices due to limited resources and knowledge.